Facebook use and personalization among Malaysian politicians during the 14th Malaysian general election / Shafizan Mohamed, Kamaruzzaman Abdul Manan and Wan Norshira Wan Mohd Ghazhali. - Mohamed, Shafizan; Abdul Manan, Kamaruzzaman; Wan Mohd Ghazhali., Wan Norshira (Faculty of Communication and Media Studies, Universiti Teknologi MARA, 2019)
Politicians today are very much reliant on Facebook to communicate with the public and promote their political ideologies. In an attempt to explore how the politicians use Facebook during election campaigns, this article explores official Facebook posts by three prime ministerial candidates during the 14th Malaysian General Election. Content analysis of the candidates’ Facebook posts showed that they strategically use Facebook to create and maintain a positive image rather than promoting issues and engaging in discussions with the public. The candidates differed in terms of the amount of posts but had minor differences in the characteristics of their Facebook contents. All of them focused on promoting their personal image suggesting that Facebook is encouraging the personalization of politics.